Combined decellularisation and dehydration improves the mechanical properties of tissue-engineered sinews - Claire Lebled; Liam M Grover; Jennifer Z Paxton (Journal of Tissue Engineering, 2014)
Novel sources of replacement sinews are needed to repair damaged tissue after injury. The current methods of repair ultilise autografts, allografts or xenografts, although each method has distinct disadvantages that limit their success. Decellularisation of harvested tissues has been previously investigated for sinew repair with the long-term aim of repopulating the structure with autologous cells. Although this procedure shows promise, the demand for donor scaffolds will always outweigh supply. Here, we report the fabrication of fibrin-based tissue-engineered sinews, which can be decellularised, dehydrated and stored. The sinews may then be rehydrated and repopulated with an autologous cell population. In addition to enabling production of patient-specific implants, interestingly, the process of combined decellularisation, dehydration and rehydration enhanced the mechanical properties of the sinew. The treated sinews exhibited a 2.6-fold increase in maximum load and 8-fold increase in ultimate tensile strength when compared with the control group ( p < 0.05 in both cases).